Coping Strategies for Multitasking Challenges of Career Women in Colleges of Education in Anambra State. - C .A, Ejeabukwa; P. N., Ezema (Journal of Home Economics Research, 2024)
The study determined the multitasking challenges and coping strategies of dual career women in tertiary institutions in Anambra State. A sample of 450 academic staff of colleges of education in Anambra State was used in the study. A 25-item questionnaire was constructed to survey the respondents on career-related, personal care related, and family responsibilities related challenges as well as coping strategies, of career women. Data obtained were analyzed using frequency, mean and standard deviation. The findings were that career women faced career-related and family related challenges to a high extent while personal-care challenges were to a low extent. The study recommended among others, proper time management, family support, networking, flexible work hours as strategies to assist the career women cope with multitasking.